Temporal lobe epilepsy surgery: What do patients want to know? - Choi, Hyunmi; Pargeon, Kim; Bausell, Rebecca; Wong, John B.; Mendiratta, Anil; Bakken, Suzanne (Epilepsy & behavior, 2011)
Patients with pharmacoresistant temporal lobe epilepsy (TLE) contemplating brain surgery must make a complex treatment decision involving trade-offs. Patient decision aids, containing information on the risks and benefits of treatment interventions, increase patient knowledge and facilitate shared decision making between patients and physicians. We conducted five focus groups to describe the information patients need to make informed decisions about TLE surgery. Twenty patients who had undergone TLE surgery described the information used in their decision-making process, and evaluated the potential for a patient decision aid to assist other patients who are considering surgery. Thematic analysis revealed information needs that were both experiential (i.e., learning about other patients’ experiences through testimonials) and factual (i.e., individualized statistical information). Patients also made suggestions on how this information should be delivered to patients. These data will accelerate the development of a patient decision aid designed to assist TLE patients in their decision making about epilepsy surgery. ► Patients who had undergone temporal lobe epilepsy surgery described the information used in their decision-making process. ► Patients expressed a need for experiential (i.e., other patients’ experiences) information. ► Patients also described a need for factual (i.e., individualized statistical) information.